Strand 3: The Tutorial: Combining Asynchronous and Synchronous Learning - Procter, Paula M. (Proceedings of the International Conference on Networked Learning, 1998)
In order to achieve effective delivery and receipt of key course components, it was decided to embrace the use of support information and communication technologies for the delivery and receipt of tutorials. The drive for the development arose from a need to embrace student centred learning at a distance, whether that distance was 3 feet or 3,00 miles. The solution was tested on different study groups within the profession of nursing. Description of the teacher and student preparation is given. Outlines of the four individual elements of the technology employed, these being video conferencing (not PC to PC), electronic mail, on-line discussion forum and file store. The significance of using a combination of the media will be highlighted. The methodology employed for teachers to assist in preparing content materials for use during the tut0rial and the competencies required for managing the on-line discussion and video conference elements. In each area the option for synchronous as against asynchronous learning will be explored. The implementation of the tutorial will be described, showing how this methodology differs from traditional tutorials. Consideration will be given to the teacher and student input over the one week duration of the tutorial. Student responses will be given and issues arising from their comments will be highlighted. Comments from teachers having been involved in the giving of tutorials by this method will also be given along with considerations for changes to teacher preparation required as a result of the paradigm shift towards embracing information and communication technologies in reaching and learning. In conclusion, the author will consider the potential for this method for lifelong learning and the possible implications chat it will have upon traditional summative assessment and approaches to student environments.